RNAi-mediated silencing of a pyruvate dehydrogenase kinase enhances triacylglycerol biosynthesis in the oleaginous marine alga Nannochloropsis salina - Ma, Xiaonian (Sci Rep, 2017)
Oleaginous microalgae have been emerging as the third-generation feedstocks for biofuel production. Genetic manipulation for improving triacylglycerol (TAG) accumulation represents a promising approach towards the economics of microalgal biofuels. Acetyl-CoA, the essential carbon precursor for de novo fatty acid biosynthesis, can be derived from pyruvate catalyzed by pyruvate dehydrogenase, which is negatively regulated by pyruvate dehydrogenase kinase (PDK). In the present study, we characterized a PDK gene (NsPDK) from Nannochloropsis salina. Subcellular localization assay assisted by green fluorescence protein (GFP) fusion indicated the localization of NsPDK in mitochondria of N. salina cells. NsPDK knockdown via RNA interference strategy attenuated NsPDK expression at the mRNA level and its enzymatic activity in vivo, leading to faster TAG accumulation without compromising cell growth under high light stress conditions. Interestingly, the TAG increase was accompanied by a decline in membrane polar lipids. NsPDK knockdown also altered fatty acid profile in N. salina. Furthermore, transcriptional analysis suggested that the carbon metabolic pathways might be influenced by NsPDK knockdown leading to diverted carbon flux towards TAG synthesis. Taken together, our results demonstrate the role of NsPDK in regulating TAG accumulation and provide valuable insights into future manipulation of oleaginous microalgae for improving biofuel production.